2014
DOI: 10.3390/atmos5030536
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variability of Atmospheric Total Gaseous Mercury in Windsor, ON, Canada

Abstract: Atmospheric Total Gaseous Mercury (TGM) concentrations were monitored in Windsor, Ontario, Canada, during 2007 ), suggesting 10% of TGM in Windsor was attributable to emissions from industrial sectors in the region. Directional TGM concentrations also indicated southwesterly air masses were TGM enriched due to emissions from coal-fired power plants and industrial facilities. Correlation and principal component analysis identified that combustion of fossil fuel, ambient temperature, wind speed, synoptic system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
4
13
0
Order By: Relevance
“…All papers reported differences between the subsets and between the full data set and the subsets to some extent (Gao, 2007;Parsons et al, 2013, Xu et al, 2014. In the 2007-2011 Windsor, Ontario, TGM study (Xu et al, 2014), seasonal PCA revealed that the transport component seems to be very influential to TGM concentrations due to high winds. The impact of GEM oxidation was more easily extracted from the springtime data because there are less confounding factors, e.g., re-emission of GEM.…”
Section: Pca Results From Data Subsetsmentioning
confidence: 99%
See 3 more Smart Citations
“…All papers reported differences between the subsets and between the full data set and the subsets to some extent (Gao, 2007;Parsons et al, 2013, Xu et al, 2014. In the 2007-2011 Windsor, Ontario, TGM study (Xu et al, 2014), seasonal PCA revealed that the transport component seems to be very influential to TGM concentrations due to high winds. The impact of GEM oxidation was more easily extracted from the springtime data because there are less confounding factors, e.g., re-emission of GEM.…”
Section: Pca Results From Data Subsetsmentioning
confidence: 99%
“…The Canadian sites are located in Point Petre and Egbert, Ontario (Blanchard et al, 2002); CAMNet stations (Temme et al, 2007), Toronto (Cheng et al, 2009), northwestern Ontario (Cheng et al, 2012); Kejimkujik National Park (Cheng et al, 2013a); Flin Flon, Manitoba (Eckley et al, 2013); Fort McMurray, Alberta (Parsons et al, 2013); and Windsor, Ontario (Xu et al, 2014). The US sites included south Florida (Graney et al, 2004); Detroit, Michigan (Lynam and Keeler, 2006;Liu et al, 2007); Mount Bachelor, Oregon (Swartzendruber et al, 2006); Athens, Ohio (Gao, 2007); Rochester, New York (Huang et al, 2010); and Grand Bay, Mississippi (Ren et al, 2014).…”
Section: Source Apportionmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Wintertime annual maximums were probably attributed to more coal combustion to produce energy for space heating, less oxidation of GEM (Stamenkovic et al, 2007), and periods of cold and stagnant air probably leading to buildup of pollution and more Hg evasion prompted by wet conditions (Peterson et al, 2009). Temporal variations in GEM concentrations could be attributed to the combined influence of environmental variables, anthropogenic sources, photochemistry, and regional transport (Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%